Korelasi Minat Anak Keluarga Petani dan Non Petani Dalam Melanjutkan Pendidikan Ke Perguruan Tinggi Terhadap Faktor Penyebab Penghasilan Dengan Metode Apriori (Studi Kasus: Desa Pasar VIII Namo Terasi) - Karonika Br Barus; Novriyenni; Magdalena Simanjuntak (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The decrease in an individual's interest in learning is caused by various factors. One of them is social factors which in some conditions cause individuals to feel inferior to continue their education to a higher academic realm. For some people, the farming profession is often underestimated, causing the social value of the farming profession to decline, causing the next generation of farmers to feel insecure to continue their education to a higher stage. From the test results on 24 samples of village data in the Pasar VIII Namo Terasi village office using the a priori method, it was found that there was 1 rule, namely If the parent's occupation is a civil servant and the income is above 4 million, the child will go to college with a supporting value of 20.8%, confidence value of 50%.